The remainder theorem says that dividing a polynomial f(x) by a 1st-degree polynomial g(x) = x - c leaves a remainder of exactly f(c).
(a) With f(x) = px ³ + 4x - 10 and d(x) = x + 3, we have a remainder of 5, so
f (-3) = p (-3)³ + 4(-3) - 10 = 5
Solve for p :
-27p - 12 - 10 = 5
-27p = 27
p = -1
(b) With f(x) = x + 3x ² - px + 4 and d(x) = x - 2, we have remainder 8, so
f (2) = 2 + 3(2)² - 2p + 4 = 8
-2p = -10
p = 5
(you should make sure that f(x) was written correctly, it's a bit odd that there are two x terms)
(c) f(x) = 2x ³ - 4x ² + 6x - p, d(x) = x - 2, R = f (2) = 18
f (2) = 2(2)³ - 4(2)² + 6(2) - p = 18
12 - p = 18
p = -6
The others are done in the same fashion. You would find
(d) p = 14
(e) p = -4359
(f) p = 10
(g) p = -13/2 … … assuming you meant f(x) = x ⁴ + x ³ + px ² + x + 20